Safe sailing: GSM and GPS controlled autonomous boat with overweight detection and obstacle avoidance - Shadman Sakib Arnob; Adiba Sumaiya Khan; Rashed Shelim; Mahmood Chowdhury (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper aims to save thousands of lives by proposing a novel technique of ensuring the complete safety of medium-sized aquatic vehicles using innovative ideas as well as augmented adaptations of myriad existing technologies. The proposed system incorporates a warning and danger level detection circuit using transistors for switching purposes when the vehicles are overloaded, and a Global System for Mobile (GSM) based module so that the control room can receive alerts and control the engines of such vehicles centrally. A system for detecting and avoiding obstacles is made using ultrasonic radar with ultrasonic transducer JSN SR04t mounted on top of SG90 servo arm which rotates to detect any obstacles. When an obstacle is detected, two other ultrasonic sensors SR-04 gets activated which are placed on two sides of the aquatic vehicle and the ultrasonic transducer becomes fixed on the exact centre. All the three sensors work together to find a free path for the boat to travel. If there is no free path, the boat will stop and wait for the paths to get cleared. The location of the vehicle is tracked by the Global Positioning System (GPS) and a Proportional-Integral-Derivative (PID) controller has been included along with a system which uses values from the GPS module to come back to its original path if it deviates from the original path when avoiding obstacles. A barcode system has been added where it keeps a count on the passengers. The tickets for the vehicle will have barcodes on them which will let the passengers in only if the barcode matches. This is used mainly to keep track of how many people are boarding the vehicle and to prevent those without tickets from boarding.